CODE STEMI Program Improves Clinical Outcome in ST Elevation Myocardial Infarction Patients: A Retrospective Cohort Study - Ginanjar, Eka (Open Access Emerg Med, 2020)
PURPOSE: One of the most frequent causes of cardiac mortality is ST elevation myocardial infarction (STEMI). Delay in the management of STEMI patients is a cause of high mortality and morbidity. This study aims to determine the effect of the implementation of the CODE STEMI program on major adverse cardiac events (MACE) and mortality of STEMI patients at Dr. Cipto Mangunkusumo General Hospital. PATIENTS AND METHODS: This was a retrospective cohort study that enrolled 207 STEMI patients who underwent primary percutaneous coronary intervention (PPCI) in 2015–2018. The patients were divided into two groups. The first group was treated prior to establishing the CODE STEMI program. The other group was treated according to the program, which was implemented in January 2017. Data were collected from medical records, and we retrospectively analyzed all in-hours, MACE, and mortality of STEMI patients from both groups as primary outcomes. Data analysis was done using the Mann–Whitney and chi-square test. RESULTS: There were 72 and 135 patients in the pre‐CODE STEMI and CODE STEMI groups, respectively. D2BT was significantly reduced by 130 min (288±306 vs 158±81, P< 0.001) since the implementation of CODE STEMI program. There were trends to lower in-hospital mortality rates (8.3% vs 4.4%, RR = 0.53) and MACE at 30 days (48.61% vs 37.78%, RR = 0.77). CONCLUSION: Implementation of the CODE STEMI program can reduce door-to-balloon time and decrease the MACE and mortality rate in STEMI patients in general hospitals.